Electron induced nanoscale engineering of rutile TiO2 surfaces. (9th November 2018) - Humphrey, David S; Pang, Chi L; Chen, Qiao; Thornton, Geoff
Abstract: Electron stimulated modifications of the rutile TiO2 (110) surface have been investigated using scanning tunnelling microscopy tip pulses and electron beam irradiation. Tip pulses on the 'as-prepared' surface induce local surface reconstruction and removal of surface hydroxyls in a region around the reconstruction. A defocused beam from an electron gun as well as tip pulses have been used to generate a number of oxygen deficient surfaces. All tip pulse features display an oval profile, which can be attributed to the anisotropic conductivity of the TiO2 (110) surface. A novel oxygen deficient phase with well-ordered defective 'nano-cracks' has been identified, which can be produced by either electron beam irradiation or low flash anneal temperatures (∼570 K). Annealing such surfaces to moderate temperatures (∼850 K) leads to mixed 1 × 1 and 1 × 2 surfaces, until now only achievable by annealing in oxygen or ageing by repeated sputter/anneal cycles. Heating to normal preparation temperatures (1000 K) reforms the clean, well-ordered 1 × 1 surface termination. Our results demonstrate the potential of electron induced processes to modify the oxygen composition and structure of the TiO2 (110) surface in a controllable and reversible way for selective surface patterning and surface reactivity modification.